Thrombophilic Risk Factors with Valproic Acid - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2009)
Thrombophilic risk factors were investigated in 21 children (age range, 1-13 years) with epilepsy and recently treated with valproic acid monotherapy, in a study at Ankara University Medicine Faculty, Turkey.